DECIPHERING FINLAND’S PIVOT: NEOCLASSICAL REALISM AND THE DECISION TO JOIN NATO IN 2022 - Darmawan, Arthamevya Zherlindya Putri; Munabari, Fahlesa; Saputro, Pradono Budi (Intermestic: Journal of International Studies, 2025)
This study examines Finland’s decision to join NATO in 2022 through the lens of Neoclassical Realism, analyzing the interplay between systemic threats and domestic political factors. Employing qualitative methods, including literature review and expert interviews, the research investigates how shifts in regional power dynamics, fueled by NATO’s eastward expansion and Russia’s military actions, created systemic pressures. Concurrently, domestic media framing, public opinion, and elite debates mediated these external influences, shaping Finland’s foreign policy response. Findings reveal that the convergence of systemic security threats and domestic political dynamics prompted a strategic pivot, illustrating the significance of domestic actors and perceptions in small state foreign policy under conditions of systemic threat. This research advances understanding of alliance formation by integrating systemic and domestic-level analyses, contributing valuable insights into regional security and NATO’s evolving role in Europe.